UK stillbirth trends in over 11 million births provide no evidence to support effectiveness of Growth Assessment Protocol program. (7th April 2020) - Iliodromiti, S.; Smith, G. C. S.; Lawlor, D. A.; Pell, J. P.; Nelson, S. M.
ABSTRACT: Objective: Use of the Growth Assessment Protocol (GAP) has increased internationally under the assumption that it reduces the stillbirth rate. The evidence for this is limited and based largely on an ecological time‐trend study. Discordance in the uptake of the GAP program between Scotland and England/Wales enabled us to assess the assertion that implementation of GAP leads to a reduced stillbirth rate. Methods: We analyzed data from the National Records for Scotland and the Office for National Statistics on the number of singleton maternities and stillbirths in Scotland and in England and Wales, respectively, from 1 January 2000 to 31 December 2015. National uptake of the GAP program over time in each of the regions was recorded. Stillbirth rate per 1000 maternities was calculated, according to year of delivery, and compared between Scotland and England/Wales. Results: During the study period, there were 870 632 singleton maternities in Scotland, of which 4243 were stillbirths, and there were 10 469 120 singleton maternities in England and Wales, of which 51 562 were stillbirths. There was a marked difference in uptake of the GAP program between the two regions, with substantially fewer maternity units in Scotland implementing the program. Stillbirth rates were static up to 2010, with a decline thereafter in both regions, to 3.75 (95% CI, 3.25–4.30) per 1000 maternities in Scotland and 4.30 (95% CI, 4.15–4.46) per 1000 maternities in England and Wales in 2015. From 2010 onwards, the decline in Scotland was faster, equating to 48 (95% CI, 47.9–48.1) fewer stillbirths per 100 000 maternities in Scotland than in England and Wales from 2010 to 2015 compared with 2000 to 2009. Conclusions: We observed a decline in stillbirth rate in England and Wales, which coincided with implementation of the GAP program. However, a concurrent decline in stillbirth rate was observed in Scotland in the absence of increased implementation of GAP. The secular rates of change in stillbirth rate in England and Wales cannot be used to infer efficacy of the GAP program. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.